Manajemen Publik dalam Pengelolaan Kawasan Wisata Pantai Anyer pada Kecamatan Anyer Kabupaten Serang : Manajemen Publik dalam Pengelolaan Kawasan Wisata Pantai Anyer Berdasarkan Perda No.8 Tahun 2014 Kabupaten Serang - Eli Apud Saepudin (TOBA: Journal of Tourism, Hospitality, and Destination, 2023)
The purpose of the research is to understand the policies and strategies implemented by the government in managing the Anyer Beach Tourism Area and to assess the effectiveness and efficiency of these policies and strategies. The research method used in this research is descriptive qualitative method with interview method and literacy study. Research Results Utilization of resources owned to improve community welfare, both in terms of income, employment opportunities, business opportunities, access to policy making, competitiveness, and increasing the human development index. The development carried out must realize sapta charm, namely: Security, Order, Cleanliness, Coolness, Beauty, Friendliness and Peace. The Village Law mandates the preparation of the Village Medium-Term Development Plan (RPJM Desa) and the Village Annual Development Plan (RKP Desa) to the village government. The Village RPJM is a plan for village development activities for a period of 6 (six) years, and the Village RKP as an elaboration of the Village RPJM is valid for a period of 1 (one) year. The Village RPJM and Village RKP are the basis for village development with the aim of making efforts to improve the quality of life and living for the greatest welfare of the village community.